Enhancing energy efficiency and long-term durability of vanadium redox flow battery with catalytically graphitized carbon fiber felts as electrodes by boron doping. (10th October 2022) - Yang, Inchan; Lee, Sora; Jang, Dawon; Lee, Jung-Eun; Cho, Se Youn; Lee, Sungho
Abstract: A boron doping on a commercial carbon fiber felt (CFF) is used to assemble a high-performance vanadium redox flow battery (VRFB). The CFF is immersed in the boric acid solution and subjected to a heat-treatment up to 2700 °C. The crystallinity of the boron-doped samples increases more than threefold when compared to only heat-treated CFF, indicating that boron induces CFF to highly graphitized CFF. As a result, electrochemical impedance spectroscopy and cyclic voltammetry reveal that boron-doped CFFs increase electrical conductivities. In addition, when the boron-doped CFFs are applied to VRFB electrodes, their electrochemical performances are improved compared to CFF and only heat-treated CFF. The CFFB5 that is a sample containing 0.6 at.% of boron contents exhibits the best electrochemical performance in the single-cell test compared to the other samples. In particular, the CFFB5 sample provides excellent energy efficiency (90% at 50 mA cm –2 ) and long-term durability (98.1% over 150 cycles). Consequently, our approach introduces effective modulation of commercially available CFF with a significant graphitization via a feasible boron doping method and we conclude that the resulting boron-doped CFF induces improved electrochemical performance for VRFB applications when the appropriate amount of a doping agent is provided. Graphical abstract: Image, graphical abstract